Geographical Variation, Gender and Interleukin 8 Relationships with Appendicitis in Residents of Niger Delta Region of Nigeria (African Journal of Biomedical Research, 2023)
Appendicitis is characterized by inflammation of the vermiform appendix accompanied by systemic inflammatory response in humans. In most cases, emergency surgical intervention is required becauseit is the leading general surgical cause of death. Nevertheless, accurate diagnosis is still a challenge because of the variation in its manifestations. This work evaluated the role of gender, seasonal variation and the immunohistochemical expression of IL-8 cytokine in appendicitis patients attending Federal Medical Centre (FMC), Yenagoa. A total of 313 appendicitis patients were recruited for the study from January 2015 to December 2020.  Results shows that seasonal variation affect appendicitis outcome with statistically significant increase in number of cases recorded in summer compared to winter. Females presented with more cases than males among subjects studied, accounting for 56.9% (n = 178) and males 43.1% (n=135) of survey subjects. Interleukin 8 was markedly expressed in the appendicitis tissue across age, gender and seasons. The study observed the clinical relevance of interleukin 8 in the prediction or diagnosis of appendicitis within the population studied. Risk factors should be monitored more in summer to reduce the occurrence of appendicitis in human population.